Reflection from the perspective of new reflectors: investigating what teacher learners find valuable in a reflective task. Issue 2 (4th March 2021) - Hunter, Duncan
ABSTRACT: This paper aims to understand the experience of reflective activity from the perspective of Teacher Learners (TLs) encountering reflective ideas for the first time. By identifying elements of a pedagogic reflective task they found most valuable and plausible, the study seeks to provide insights to improve educators' presentation of reflective ideas. It investigates the experiences of 20 language teachers writing reflections on classroom teaching during a programme of formal instruction. Writers' decisions are examined intensively to identify which phases/elements of an idealized cycle they chose to extend while engaged in a reflective task. Writers' commentaries on their writing, collected after the period of their instruction, were also analysed to discover the elements they found plausible and valuable beyond their utility for the course. The study found that writers looking back at their accounts tended to locate most value in practical, 'descriptive' sections of their writing rather than those linking to academic theory, or more 'critical' modes of reflection. Nevertheless, interviewee responses indicated that many had a nuanced sense that such higher-level modes of reflection might have value outside the formal circumstances of the programme. The paper finally offers practical suggestions that respond to these findings.